Total microbial and phosphate-solubilizing population in soil submitted to different cultivation systems - Barroti, Giovane; Nahas, Ely (Pesquisa Agropecuaria Brasileira, 2000)
The objective of the present study was to evaluate the effect of different plant species, phosphorus sources, and liming on the total microbial and phosphate-solubilizing population. In order to achieve that, bacteria and fungi capable of solubilizing hydroxyapatite providing available P were isolated. An experiment was carried out in a randomized factorial block design 3x3x2. The factors evaluated were plant species (control, Brachiaria ruziziensis and Cajanus cajan), fertilizers (control, simple superphosphate and rock phosphate, both at the dose of 400 kg ha-1 of P205) and liming (with and without lime). While the bacterial population increased due to the effect of liming, the fungal population also increased independently of liming in the soil cultivated with B. ruziziensis and fertilized with superphosphate. An increase of the microbial biomass-P compared to the control was observed under the influence of B. ruziziensis (23.9%), superphosphate (30.9%) or liming (46.9%). The number of solubilizing bacteria was favored by liming and by the planting of C. cajan fertilized with rock phosphate or with unfertilized B. ruziziensis. The solubilizing fungi increased in the absence of plants or fertilization and in the presence of C. cajan fertilized with rock phosphate. Finally, liming enhanced more the growth of solubilizing fungi than did the control in the treatments using rock phosphate, B. ruziziensis or C. cajan.
Keywords: Brachiaria ruziziensis; Cajanus cajan; bacteria; fungi; biomass